2018
DOI: 10.1108/pr-07-2017-0221
|View full text |Cite
|
Sign up to set email alerts
|

Job engagement in higher education

Abstract: Purpose Employees’ job engagement is a key driver for organizational success and competitive advantage. Based on Kahn’s engagement theory and social exchange theory, the purpose of this paper is to examine the relationships between job engagement, transformational leadership, high-performance human resource (HR) practices, climate for innovation, and contextual performance. Design/methodology/approach A questionnaire survey, conducted at two different points in time, was employed to collect data from 394 pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 69 publications
(73 reference statements)
1
66
0
Order By: Relevance
“…First, this study provides an empirical support of the theoretical relationship between organizational climate and morale, and CJE -the relationship which is recently identified meagre to date in the literature (Ancarani et al, 2019). Moreover, it attempts to answer research call of (Pham-Thai et al, 2018) to investigate three antecedents of CJE of academic staff of higher education. Second, unlike previous authors, it is among the first to reveal a reverse lens between OCB-I and CJE by suggesting that OCB-I can have a direct and positive effect on CJE.…”
Section: Theoretical and Methodological Contributionsmentioning
confidence: 64%
See 2 more Smart Citations
“…First, this study provides an empirical support of the theoretical relationship between organizational climate and morale, and CJE -the relationship which is recently identified meagre to date in the literature (Ancarani et al, 2019). Moreover, it attempts to answer research call of (Pham-Thai et al, 2018) to investigate three antecedents of CJE of academic staff of higher education. Second, unlike previous authors, it is among the first to reveal a reverse lens between OCB-I and CJE by suggesting that OCB-I can have a direct and positive effect on CJE.…”
Section: Theoretical and Methodological Contributionsmentioning
confidence: 64%
“…Gaining and sustaining a competitive advantage in today's hypercompetitive era are confounding challenges for organizations (Pham-Thai, McMurray, Muenjohn, & Muchiri, 2018) because the dynamic and professional work environment have substantially challenged the conventional view of measuring employee performance (Eldor & Harpaz, 2016). Universities are the hub of highly-qualified individuals where they are engaged in various educational pursuits e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This further supported the notion of Ramasamy and Abdullah (2017) where employee disengagement in the universities may result in loss of progress for the institutions. Despite the issue that has been frequently highlighted in the mass-media and government official reports, empirical studies on employee engagement are still limited in developing countries (Bailey, Madden, Alfes, & Fletcher, 2017) and studies on the HEIs require further investigation (Pham-Thai, McMurray, Muenjohn, & Muchiri, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the authorities of these private universities of Bangladesh including UGC seem ineffective in improving quality education (Ashraf et al, 2009;Joarder, 2012;Ashraf et al, 2016). In fact, except a few, in most of the private universities, quality of education has been staggering in unfathomed quagmires inflicted by unplanned and improper human resource management practices for which the faculty turnover rate in these universities is very high (Ashraf, 2009;Jalil, 2009;Joarder, 2012;Ashraf et al, 2016;Imran et al, 2017;Wong and Wong, 2017;Pham-Thai et al, 2018). This high faculty turnover rate intuitively implies a lack of organisational commitment behaviour of the faculty members (Joarder, 2012;Imran et al, 2017;Kokubon, 2018;Sutherland, 2018).…”
mentioning
confidence: 99%